Factors affecting customer loyalty through satisfaction towards retail marketing strategy: an exploratory investigation on Malaysian hypermarkets - Haque, A. K. M. Ahasanul (INSI Publications, 2014)
Background: Today, global market is targeted by so many established retailers, because they are looking for new potential market expansion. Malaysian hypermarkets are growing drastically challenging in the past decades; as a result customer satisfaction and customer loyalty has become a critical phenomenon. Objective: The main purpose of this study is to measure customers‟ loyalty through satisfaction towards retail marketing strategy in Malaysian hypermarkets perspective. Methodology: In this study, resource based theory has been exploited for developing conceptual research framework. The data has been collected by distributing self-administered questionnaire among 350 consumers involving different races in Malaysian hypermarkets in Kuala Lumpur through convenience sampling method. The data analysis has been conducted using descriptive statistics as well as exploratory and confirmatory factor analysis. Subsequently, by using AMOS through structural equation modeling, 292 valid cases have been selected to test the hypothesized relationship among the variables in the research conceptual model. Results: The results revealed that service quality, product quality, price strategy and store attribute have significant relationship with customer satisfaction and importantly customer satisfaction has ABSTRACT